Strengthening Fiscal Independence: The Role of Regional Original Revenue and Research-Based Budget Priorities in Funding Central Kalimantan's RPJMD Program for Inclusive Welfare - Sastori Aryanto; Wiwin Zakiah; Benius Benius (PT FORMOSA CENDEKIA GLOBAL, 2026)
Fiscal autonomy is a fundamental prerequisite for regions to implement sustainable and equitable development. This article analyzes strategies for strengthening the fiscal autonomy of Central Kalimantan Province (Kalteng) by focusing on optimizing Local Own-Source Revenue (PAD) and implementing research-based budget priorities to fund programs in the Regional Medium-Term Development Plan (RPJMD). This research uses a qualitative approach with a case study method, through secondary data analysis from Regional Budget (APBD) documents, RPJMD, and related literature. The findings indicate that Central Kalimantan's revenue structure still depends on central government transfers, with a relatively limited contribution from PAD. Potential PAD sources such as local taxes, levies, and natural resource management have not been maximized. Furthermore, the budgeting process has not fully internalized research evidence as a basis for setting priorities, potentially leading to inefficiencies. This article proposes an integrative strategic framework covering: (1) diversification and intensification of the PAD base with a green economy approach; (2) strengthening local government fiscal capacity; (3) institutionalization of an Evidence-Based Planning and Budgeting System; and (4) strengthening public accountability and participation.